National Strike, Special Conference, 20 January 1927 (page 8)
1927-01-20 "National Strike, Special Conference, 20 January 1927 (page 8)" [g0496008.jpg], 20 January 1927, Trades Union Congress Report of proceedings at a Special Conference of Executives of all affiliated unions to consider the Report of the General Council on the National Strike, held at the Central Hall, Westminster, on Thursday 20 January 1927.